Remembering and Lamenting Lost Liturgy: The Text and Context of Rites of Durham, c.1593. (September 2019) - Spinks, Bryan D.
The Rites of Durham was written c.1593, and the authorship is uncertain, but is presumed to be a compilation of accounts by one or more of the former monks and clergy who lived through the dissolution and who remained either at the cathedral or in Durham parishes after the Elizabethan Settlement. Rites gives detailed descriptions of the cathedral furnishings and of the processions and festivals prior to the dissolution when the shrine of St. Cuthbert was still intact. The account shows a bias against the further reforms made under Dean William Whittingham. It is not, however, a Customary, and has inaccuracies and biases. It is most certainly a liturgical anamnesis, and a lament for a lost liturgical past. The compiler, though, may have intended it as a testimony of the past which might one day be restored.